Preliminary Study On Soil Collembola In An Area Attacked By Pyroclasttc Flow - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Abstract: Study on soil collembola in an area attacked by pyroclastic flow was conducted at Boyong riverbank. The attacked was on 22 November 1994, and the study was in March to October 1995. The study area was divided into three habitats. They were the sandy habitat, formerly solid materials of the pyroclastic flow, the lower bank, relatively flat and formerly dominated by grasses, and the upper bank, steep and formerly dominated by pine trees and broad leaf herbs. Apparently, soil collembola of Sminthuridae, Entomobryiidae, and Isotomidae were able to immigrate to the sandy habitat, but they were not able to establish yet. Soil collembola in the lower and upper banks were able to rehabilitate. There was also an indication that there were individuals of Onychiuridae, and Hypogastruridae escaped from the effect of pyroclastic flow. There was possibility also that few individuals of Sminthuridae, Entomobryiidae, and Isotomidae could survive. They were then able to recolonized in the habitats.